Challenges and Opportunities for Modernizing the National Violent Death Reporting System. - Mays, Vickie M.; Cochran, Susan D. (American Journal of Public Health, 2019)
The article reponsds to an issue article on the coding of self-identified sexual orientation and gender identity (SOGI) in the U.S. National Violent Death Reporting System (NVDRS). Topics include attempts by the U.S. National Center for Health Statistics to modernize the U.S. National Vital Statistics System, the collection of data from electronic health records (EHRs), and the significance of interoperability between various data sources.